2019
DOI: 10.1039/c9ra08354e
|View full text |Cite
|
Sign up to set email alerts
|

Different phase-dominated chiral assembly of polyfluorenes induced by chiral solvation: axial and supramolecular chirality

Abstract: The chiral solvation induced chirality in achiral polyfluorenes showed the axial chirality for PF2/6 with branched side alkyl chain, but supramolecular chirality for PF8 with linear side alkyl chain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…CD spectroscopy is the most commonly used and effective method for characterizing supramolecular chirality. [79][80][81][82] The CD graph is drawn by taking the wavelength λ as the abscissa and the difference in absorption coefficient Δε = (ε L − ε R ) as the ordinate. The resulting spectrum is the circular dichroic spectrum.…”
Section: Supramolecular Chirality In Polymer Aggregatesmentioning
confidence: 99%
“…CD spectroscopy is the most commonly used and effective method for characterizing supramolecular chirality. [79][80][81][82] The CD graph is drawn by taking the wavelength λ as the abscissa and the difference in absorption coefficient Δε = (ε L − ε R ) as the ordinate. The resulting spectrum is the circular dichroic spectrum.…”
Section: Supramolecular Chirality In Polymer Aggregatesmentioning
confidence: 99%
“…When achiral guests interact with chiral hosts, chiral information from chiral sources can be transferred to the achiral systems to form supramolecular chiral assemblies. Many chiral sources have been extensively studied including CPL [ 69 , 70 ], chiral additives [ 71 , 72 , 73 ], chiral solvents [ 74 , 75 , 76 , 77 , 78 ], chiral gelators [ 79 , 80 , 81 ], DNA [ 82 ], or chiral nanostructures [ 83 , 84 , 85 , 86 ].…”
Section: Basic Concepts Related To Supramolecular Chiralitymentioning
confidence: 99%
“…[29,30,36] It has previously been shown that chirality can be induced into β-phase PFO solution aggregates through control of the heating/cooling rate, solvent, and solution concentration. [39,40] Despite these exciting observations, the induction of chiroptically active β-phase (hereafter "chiral β-phase") domains into thin PFO films has not been previously reported, which lies central to the realization of high-performance CP-emitting PFO devices operational in the deep-blue spectral region. Here, we show that the chiral small molecule 1-aza [6]helicene (aza [6]H) can induce a chiral phase in crystalline PFO (circular dichroism, CD ≈ −10 800 mdeg) upon TA (T = 160 °C).…”
Section: Introductionmentioning
confidence: 99%